Intervención fisioterapéutica en niños con síndrome de Angelman - Moyolema Torres, Luis Miguel (2023)
SUMMARY The documentary research was developed by collecting data or information, whose objective is to analyze the importance of physiotherapeutic intervention in children with Angelman Syndrome (AS) to obtain the most appropriate treatment. Angelman syndrome is a genetic disorder that affects chromosome 15 as a consequence of which neurodevelopmental delays may occur. Physiotherapy is the set of methods and techniques, where physical means are applied to prevent and cure patients affected by some somatic and organic dysfunctions to maintain an adequate level of health. The physiotherapeutic intervention in AS is little known due to the few cases that occur in children and therefore there is little knowledge of physiotherapeutic treatments in health professionals. For the development of the methodology, 128 scientific articles were found, of which 35 articles in Spanish and English were selected, it could be classified by the inclusion criteria using the PEDro rating scale with a rating greater than or equal to 6. It was possible to Obtain information from scientific articles from the Scopus database, ProQuest, medical journal, Pubmed, Google Scholar, Scielo, Cochrane, PEDRo. We conclude that the physiotherapeutic intervention allows delaying the neurodevelopmental symptoms and also improves fine and gross motor skills, coordination, gait, in this way we can significantly improve the patient's lifestyle. Keywords: Angelman syndrome, Physiotherapy, UBE3A, neurodevelopmental delay